2021
DOI: 10.3390/foods10092123
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of Phenolics of Tetrastigma hemsleyanum Roots under In Vitro Digestion and Colonic Fermentation as Well as Their In Vivo Antioxidant Activity in Rats

Abstract: Tetrastigma hemsleyanum Diels et Gilg is a herbaceous perennial species distributed mainly in southern China. The Tetrastigma hemsleyanum root (THR) has been prevalently consumed as a functional tea or dietary supplement. In vitro digestion models, including colonic fermentation, were built to evaluate the release and stability of THR phenolics with the method of HPLC-QqQ-MS/MS and UPLC-Qtof-MS/MS. From the oral cavity, the contents of total phenolic and flavonoid began to degrade. Quercetin-3-rutinoside, quer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 36 publications
(70 reference statements)
0
10
0
Order By: Relevance
“…In this sense, Sun et al described the metabolism of Tetrastigma hemsleyanum roots using the colonic fermentation model and demonstrated that colonic microorganisms can decompose the (poly)phenols present in this plant, as the total phenolic and total flavonoid contents were reduced by 61% and 76% respectively. 109 Moreover, a recent study carried out by Vázquez-Rodríguez et al showed the potential of Silvetia compressa to improve human gut microbiota by the use of this model. 110 Once the effect of the gastrointestinal digestion on the release and stability of bioactive phytochemicals present in dietary plant-based foods available to be absorbed at the intestinal level is clarified, cell cultures represent an interesting predictive tool to study the capacity of bioactive compounds to cross the intestinal barrier.…”
Section: Experimental Models Of Interest To Research On Bioavailabilitymentioning
confidence: 97%
See 1 more Smart Citation
“…In this sense, Sun et al described the metabolism of Tetrastigma hemsleyanum roots using the colonic fermentation model and demonstrated that colonic microorganisms can decompose the (poly)phenols present in this plant, as the total phenolic and total flavonoid contents were reduced by 61% and 76% respectively. 109 Moreover, a recent study carried out by Vázquez-Rodríguez et al showed the potential of Silvetia compressa to improve human gut microbiota by the use of this model. 110 Once the effect of the gastrointestinal digestion on the release and stability of bioactive phytochemicals present in dietary plant-based foods available to be absorbed at the intestinal level is clarified, cell cultures represent an interesting predictive tool to study the capacity of bioactive compounds to cross the intestinal barrier.…”
Section: Experimental Models Of Interest To Research On Bioavailabilitymentioning
confidence: 97%
“…In this sense, Sun et al . described the metabolism of Tetrastigma hemsleyanum roots using the colonic fermentation model and demonstrated that colonic microorganisms can decompose the (poly)phenols present in this plant, as the total phenolic and total flavonoid contents were reduced by 61% and 76% respectively 109 . Moreover, a recent study carried out by Vázquez‐Rodríguez et al .…”
Section: Limitations Of the Diverse Experimental Models For Assessing...mentioning
confidence: 98%
“…The resultant contents then bind to starch in the digestive tract [113]. Furthermore, another study showed kaempferol glycosides degradation and absorption during gastrointestinal digestion [114]. The Nrf2 interactome is functionally linked to cytoprotection in lowgrade stress, chronic inflammation, metabolic alterations, mechanical stress, and ROS formation [115].…”
Section: Kaempferol Modification During Digestion and Colonic Ferment...mentioning
confidence: 99%
“…Modern phytochemistry shows that SYQ contains a variety of active ingredients, including flavonoids, phenolic acids, nucleosides, amino acids, polysaccharides, triterpenes, steroids, alkaloids, and other constituents [ 3 ]. Modern pharmacological research on SYQ has a variety of pharmacological effects, including antitumor, antioxidant, anti-inflammatory, antibacterial, antipyretic, analgesic, immunomodulatory, and other activities [ 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ]. Among the total phenolic acids and total flavonoids of SYQ, rutin, isoquercitrin, nicotifiorin, and astragalin are the main substances, for which metabolites in the body could explain some of the antioxidant biomarkers [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Modern pharmacological research on SYQ has a variety of pharmacological effects, including antitumor, antioxidant, anti-inflammatory, antibacterial, antipyretic, analgesic, immunomodulatory, and other activities [ 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ]. Among the total phenolic acids and total flavonoids of SYQ, rutin, isoquercitrin, nicotifiorin, and astragalin are the main substances, for which metabolites in the body could explain some of the antioxidant biomarkers [ 9 ]. Amino acids and nucleosides are usually considered to have nutritional value and health benefits [ 15 ].…”
Section: Introductionmentioning
confidence: 99%